The Tatler, 1901-1965. - Illustrated London News (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2022)
From its establishment in 1901 until 1968, The Tatler was one of various publications owned by The Illustrated London News (ILN). The magazine (founded by literary critic Clement Shorter, a former editor of the ILN) catered primarily to an affluent and traditionalist audience. Appearing on a weekly basis, and enduring two World Wars, The Tatler (known as The Tatler and Bystander from 1940) kept its readership abreast of the latest developments in British High Society.
Date range: 1901-1965.
Keywords: Popular culture -- Great Britain -- Periodicals; Great Britain -- Social life and customs -- 20th century -- Periodicals